Comparative Study of Local Administration Systems in Indonesia: Effectiveness and Transparency (International Forum of Researchers and Lecturers, 2024)
This article presents a comprehensive comparative study of local administration systems in Indonesia, emphasizing the critical dimensions of effectiveness and transparency. Utilizing a mixed-methods approach, including qualitative interviews and quantitative analysis of regional data, this research evaluates how varying policies and administrative practices influence public service outcomes across diverse localities. The study focuses on several key effectiveness indicators, such as service delivery speed, citizen satisfaction, and resource allocation efficiency. Findings reveal a significant correlation between transparency levels and administrative effectiveness, indicating that regions with robust transparency measures—such as open budget policies and public access to information—tend to achieve superior public service outcomes. Additionally, the research highlights the role of community engagement and participatory governance in enhancing both transparency and effectiveness. This study underscores policymakers' need to prioritize transparency initiatives as a foundational element for improving local administration systems. By fostering a culture of openness and accountability, local governments can better meet the needs of their constituents and enhance overall governance quality in Indonesia.